KAJIAN MAKNA DALAM KALIMAT PERINTAH (USL?B AL-AMR): STRUKTUR DAN FUNGSI: STUDY OF MEANING IN COMMAND SENTENCES (USL?B AL-AMR): STRUCTURE AND FUNCTIONS - Mohammad Yusuf Setyawan (Department of Arabic Education of State Collage for Islamic Studies of Mandailing Natal, 2021)
This article aims to reveal the structure and function of imperative sentences in Arabic using the balagah approach. Meaning is an important study in language because the purpose of language is to reach a certain meaning. In modern times, the study of meaning in Arabic is included in the realm of 'Ilm ad-Dal?lah. Even so, attention to meaning has long been carried out by Arab linguists, including balagah experts. Among the studies of meaning that are the subject of attention by balagah experts is the study of meaning in command sentences. This research is a qualitative research with content analysis method. The examples included are sourced from the Qur'an, hadith, and Arabic poems accompanied by explanations regarding the structure and function of command sentences. In this article, it is found that the command sentence in Arabic is manifested in four tools, namely fi'il amr, fi'il mu??ri' maqr?n bi l?m amr, isim fi'il amr, and ma?dar n?ib 'an fi'il amr. The original meaning of the command sentence is to ask for a job from a higher position to a lower party. However, the command sentence also contains other meanings, including to allow (ib??ah), give choice (takhy?r), threaten (tahd?d), weaken (ta'j?z), humiliate (ih?nah and ta?q?r), equalize (taswiyah), daydream (tamann?), pray (du'?), offer (iltim?s), and glorify (ikr?m). Determination of meaning in the command sentence is based on the context (siy?q) and the accompanying indicators (qar?nah).